2022
DOI: 10.1002/pen.26093
|View full text |Cite
|
Sign up to set email alerts
|

Role of expandable graphite on flame retardancy, smoke suppression, and acid resistance of polypropylene/magnesium hydroxide composites

Abstract: In this work, expandable graphite (EG) was introduced to the composite of polypropylene/magnesium hydroxide (PP/MH) by melt compounding, fire performance, thermal degradation behavior, and acid resistance of the PP/MH/EG composites were investigated. The results demonstrate that the flame retardant efficiency of MH is very low by itself and there is a noticeable synergism between MH and EG in PP. The addition of proper EG can enhance flame retardancy, smoke suppression, and acid resistance of the PP/MH composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…When the content of SR reaches 10 parts, T 5% increases to 356.2°C, which is because more SR can form a more stable structure with the amorphous region of HDPE after irradiation, and the thermal stability is improved. [ 21 ] In addition, we can see in Figure 4B that the maximum thermal decomposition temperature (T m ) of HDPE composite is similar, and there are no multiple thermal decomposition peaks due to the addition of SR, which also proves that SR can produce good compatibility with HDPE. Finally, through the content of residues, it can be found that the increase of SR content will increase the content of residues, which is because SR is easy to form inert residues such as silica after thermal decomposition, thus increasing the content of residues.…”
Section: Resultsmentioning
confidence: 76%
“…When the content of SR reaches 10 parts, T 5% increases to 356.2°C, which is because more SR can form a more stable structure with the amorphous region of HDPE after irradiation, and the thermal stability is improved. [ 21 ] In addition, we can see in Figure 4B that the maximum thermal decomposition temperature (T m ) of HDPE composite is similar, and there are no multiple thermal decomposition peaks due to the addition of SR, which also proves that SR can produce good compatibility with HDPE. Finally, through the content of residues, it can be found that the increase of SR content will increase the content of residues, which is because SR is easy to form inert residues such as silica after thermal decomposition, thus increasing the content of residues.…”
Section: Resultsmentioning
confidence: 76%
“…When MHPA and MH are added at the same time, it can be seen from the cross‐section of the HDPE/MHPA/MH composite that small MH particles fill the entire fracture surface, and the number of folds and holes increases. This is because MH is an inorganic flame retardant with poor compatibility with HDPE, an organic substance, and because MH is small in size, it is easy to agglomerate when dispersed in HDPE, which further destroys the internal structure of HDPE, so it may have a greater impact on the mechanical properties of HDPE composites 22 . If only MH is added, then it will undoubtedly cause obvious damage to the structure and mechanical properties of HDPE.…”
Section: Resultsmentioning
confidence: 99%
“…This is because MH is an inorganic flame retardant with poor compatibility with HDPE, an organic substance, and because MH is small in size, it is easy to agglomerate when dispersed in HDPE, which further destroys the internal structure of HDPE, so it may have a greater impact on the mechanical properties of HDPE composites. 22 If only MH is added, then it will undoubtedly cause obvious damage to the structure and mechanical properties of HDPE. As can be seen from Figure 4d, the addition of a large amount of MH makes HDPE/MH fracture surface produce a large number of holes, which will hinder the movement of molecular chains and inhibit the transmission of external forces, thus damaging the mechanical properties of HDPE composites.…”
Section: Sem and Eds Of Hdpe And Its Compositesmentioning
confidence: 99%
“…21 On the other hand, a common approach to further improve the flame retardancy effect is to combine MH with other flame retardants such as boron compounds, 22 metal oxides, 23 minerals 24 and carbon based materials. 25 Metal carbonates are widely preferred to be combined with MH to improve flame retardant efficiency. 26,27 Calcium carbonate (CaCO 3 ) has been extensively used to enhance thermal stability and stiffness for polymeric composites.…”
Section: Introductionmentioning
confidence: 99%